A study on the performance of cascade hard sails and sail-equipped vessels. (1st April 2015) - Li, Qiao; Nihei, Yasunori; Nakashima, Takuji; Ikeda, Yoshiho
Abstract: This study proposes a type of hard sail and investigates its potential use on commercial vessels for utilizing wind energy. We focus on the performance of cascade sails and consider the aerodynamic interaction between the sails. To obtain the lift and drag coefficients of the sails, wind tunnel testing and a two-dimensional simulation code based on the boundary element method with vortices are used. According to the change in distance and attack angle of each sail in the cascade, the best setup parameter is investigated, and the aerodynamic interaction is analyzed. From the viewpoint of the sailing performance of the vessel, our results demonstrate that cascade hard sails can significantly reduce fuel costs for commercial vessels. Highlights: A new type of hard sail was proposed considering its high performance and rig structure. A cascade of the hard sails is discussed by experiment and simulation. The best setup parameters of cascade sails are investigated and the aerodynamic interactions are analyzed. From the viewpoint of sail-equipped vessels, the ship speed, the drift angle, and the heel angle are discussed.